Virgilio barco public library. dissapearance of the city, invocation of the savanna. study of urban considerations within an architectural proyect (2006)
The article procures to reveal the existence of a complex urban event within the project for the Virgilio Barco public library. Throughout this essay, the implantation of the library is looked upon, therefore studying: the natural elements that provide it of temporality, its relationship with the surrounding landscape and its incidence over the construction of a limit. The conceived space is later studied. How does the architectural idea emerge and how is the city therefore established? What changes does it present? Of what elements and parts is it composed off and under which premises does it address a concrete formal result? Relationships and actors that participate in the composition of the floor plan are revealed. It is possible to understand the architectural project as a singular urban event because the composition appeals to diverse and seldom dissimilar elements to reconstruct at one instance, the accumulative process that makes up a city throughout a historical period, invoking in order to achieve this goal, timeless experiences and remembrances that belong to the architect.